Characteristics and outcome of patients with core-binding factor acute myeloid leukemia and FLT3-ITD: results from an international collaborative study - Kayser, Sabine; Kramer, Michael; Martínez-Cuadrón, David; Grenet, Justin; Metzeler, Klaus H; Sustkova, Zuzana; Luskin, Marlise R; Brunner, Andrew M; Elliott, Michelle A; Gil, Cristina; Marini, Sandra Casal; Ráčil, Zdeněk; et al. (Haematologica, 2022)
The aim of this study was to evaluate the prognostic impact of FLT3-ITD in core-binding factor acute myeloid leukemia (CBFAML) in an international, multicenter survey of 97 patients of whom 52% had t(8;21)(q22;q22) and 48% had inv(16)(p13q22)/t(16;16)(p13;q22). The median age of the patients was 53 years (range, 19-81). Complete remission after anthracycline-based induction (n=86) and non-intensive therapy (n=11) was achieved in 97% and 36% of the patients, respectively. The median follow-up was 4.43 years (95% confidence interval [95% CI]: 3.35-7.39 years). The median survival after intensive and non-intensive treatment was not reached and 0.96 years, respectively. Among intensively treated patients, inv(16) with trisomy 22 (n=11) was associated with a favorable 4-year relapse-free survival rate of 80% (95% CI: 59-100%) as compared to 38% (95% CI: 27-54%; P=0.02) in all other patients with CBFAML/ FLT3-ITD (n=75). Overall, 24 patients underwent allogeneic hematopoietic cell transplantation (HCT), 12 in first complete remission and 12 after relapse. Allogeneic HCT in first complete remission was not beneficial (P=0.60); however, allogeneic HCT seemed to improve median survival in relapsed patients compared to that of patients treated with chemotherapy (not reached vs. 0.6 years, respectively; P=0.002). Excluding patients with inv(16) with trisomy 22, our data indicate that compathe outcome of CBF-AML patients with FLT3-ITD may be inferior to that of patients without FLT3-ITD (based on previously published data), suggesting that prognostically CBF-AML patients with FLT3-ITD should not be classified as favorable-risk. FLT3-inhibitors may improve the outcome of these patients.
Keywords: senioři; Core Binding Factors; senioři nad 80 let; Retrospective Studies; transkripční faktor PEBP2; Prognosis; fms-Like Tyrosine Kinase 3; Remission Induction; Middle Aged; mutace; Leukemia, Myeloid, Acute; Adult; mladý dospělý; Aged, 80 and over; Hematopoietic Stem Cell Transplantation; Young Adult; prognóza; Mutation; transplantace hematopoetických kmenových buněk; retrospektivní studie; Humans; lidé středního věku; akutní myeloidní leukemie; tyrosinkinasa 3 podobná fms; indukce remise; dospělí; Aged; lidé